IN VIVO LIPID-LOWERING AND ANTI-ATHEROSCLEROTIC EFFECTS OF SCORPION TURMERIC (CURCUMA RANGJUED) EXTRACT (Tạp chí Y học Cộng đồng, 2026)
Dyslipidemia represents an independent risk factor for cardiovascular diseases, contributing to high morbidity, mortality and healthcare costs worldwide. Previous studies have indicated that improving lipid profiles can effectively prevent the onset and progression of atherosclerosis and associated CVD events. To explore alternatives to conventional lipid-lowering drugs, which often have adverse effects, this study evaluated the in vivo lipid-lowering and anti-atherogenic effects of Scorpion Turmeric (Curcuma rangjued) extract.GERC7, a honey-based emulsion prepared from steam-distilled C. rangjued rhizome extract, was administered to mice with Poloxamer-407 (P-407)-induced endogenous dyslipidemia. GERC7 significantly reduced plasma lipid levels at all tested doses compared to the disease control group, with the optimal effect observed at the highest dose (7.2 mL/kg/day), reducing total cholesterol (TC) and low-density lipoprotein (LDL) by 31% and 43%, respectively. The atherogenic index (AI), increased 4.9-fold in the disease control group compared to normal controls, but declined substantially in GERC7- and atorvastatin-treated groups. The lowest AI was observed at the 7.2 mL/kg dose, consistent with maximal lipid reduction.These findings demonstrate dose-dependent lipid-lowering and anti-atherosclerotic effects of GERC7, indicating its potential utility as a multi-target natural therapeutic option for dyslipidemia and atherosclerosis management.
Keywords: Dyslipidemia, Atherogenic Index, GERC7, Curcuma rangjued, Nghe Bo Cap